Tourism Sector Development Strategy Based on SWOT-AHP in Palu City - Erifsandi, M.; Suparman, Suparman; Tope, Patta; Yunus, Rita; Ichsan, Muhammad (Transpublika Publisher, 2025)
Palu City's tourism industry has the potential to increase local revenue, but its growth is hindered by the lack of a well-thought-out plan that considers its distinctive local features and susceptibility to natural disasters. This study aims to determine a tourism sector development strategy to support regional development in Palu City. The research method employs descriptive analysis with data collection through interviews with relevant government officials, local communities, and tourists. Data analysis was conducted using SWOT method to identify strategic position and AHP method to determine tourism development priorities. SWOT analysis results indicate that Palu City's tourism development strategy is positioned in Quadrant I with coordinates (0.35; 0.4), suggesting an SO (Aggressive) strategy. This strategy optimizes strengths and opportunities through enhancing natural and human resources quality. improving infrastructure, and supporting government policies for sustainable tourism development. AHP analysis reveals geographical conditions as the highest criterion with 54.9%, while natural tourism emerges as the priority alternative with 75.8%. These results are relevant to Palu City's geographical conditions with significant natural tourism potential. Policy implications from this study emphasize the need for Palu City government to focus on developing natural tourism by strengthening supporting infrastructure, enhancing tourism human resource capacity through continuous training, and integrating local community roles in sustainable destination management. The recommended aggressive strategy can serve as a reference for formulating effective tourism development programs that impact Regional Original Revenue (PAD) enhancement and community welfare improvement.